Risk of traumatic intracranial haemorrhage is increased in older people exposed to oral anticoagulation with phenprocoumon - Büchele, Gisela; Rapp, Kilian; Bauer, Jürgen M.; Jaensch, Andrea; Benzinger, Petra (Aging clinical and experimental research, 2020)
Hospital admissions resulting from traumatic intracranial haemorrhages (TIH) in older people are increasing. There are concerns regarding an increased risk of a TIH in people taking oral anticoagulants (OAC) like phenprocoumon.